Simulation Study of Aluminum Alloy Ribbed Member Spinning with Ultrasonic Vibration - LI Xiaokai, ZHAO Yixi, YU Zhongqi, ZHU Baohang, CUI Junhui (Shanghai Jiaotong Daxue xuebao, 2021)
Flow spinning process is beneficial to realizing the integral forming of the ribbed members, but the height of the inner rib that can be formed is limited. Therefore, an ultrasonic assisted method was introduced into the flow spinning process to increase the height of the inner rib. Uniaxial tensile and compression tests with ultrasonic vibration were conducted to establish the hardening equation of the 2219-O aluminum alloy considering the acoustic softening effect. The friction reduction effect after ultrasonic loading was analyzed. A simulation model of aluminum alloy ribbed member spinning with ultrasonic vibration was established using the Abaqus software. The simulation results show that the ultrasonic vibration can reduce the deformation resistance of the material, improve the material flow of the ribs in different directions, guide the material flowing into the rib grooves, and thereby improve the filling height of the ribs. When the amplitude reaches 12μm, the rib height can be increased by 1/3.